2019
DOI: 10.1158/1078-0432.ccr-18-3654
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Localized Costimulatory T-Cell Engagement by the 4-1BB/HER2 Bispecific Antibody-Anticalin Fusion PRS-343

Abstract: Purpose: 4-1BB (CD137) is a key costimulatory immunoreceptor and promising therapeutic target in cancer. To overcome limitations of current 4-1BB-targeting antibodies, we have developed PRS-343, a 4-1BB/HER2 bispecific molecule. PRS-343 is designed to facilitate T-cell costimulation by tumorlocalized, HER2-dependent 4-1BB clustering and activation. Experimental Design: PRS-343 was generated by the genetic fusion of 4-1BB-specific Anticalin proteins to a variant of trastuzumab with an engineered IgG4 isotype. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 41 publications
2
109
0
Order By: Relevance
“…For example, the initial clinical development of the agonistic 4‐1BB monospecific antibody urelumab was terminated due to fatal hepatotoxicity, with a maximum tolerated dose of 0.1 mg/kg q3w 18 . A 4‐1BB/HER2 bispecific molecule PRS‐343 is designed to facilitate T‐cell co‐stimulation by tumor‐localized, HER2‐dependent 4‐1BB clustering, and activation ( Figure ) 19 . In a phase I study in patients with HER2‐positive cancer, PRS‐343 demonstrated single‐agent antitumor activity, including partial responses, and was well‐tolerated at doses up to 8 mg/kg q2w 20 …”
Section: Mechanism Of Action Of Bispecific Antibodies In Oncologymentioning
confidence: 99%
“…For example, the initial clinical development of the agonistic 4‐1BB monospecific antibody urelumab was terminated due to fatal hepatotoxicity, with a maximum tolerated dose of 0.1 mg/kg q3w 18 . A 4‐1BB/HER2 bispecific molecule PRS‐343 is designed to facilitate T‐cell co‐stimulation by tumor‐localized, HER2‐dependent 4‐1BB clustering, and activation ( Figure ) 19 . In a phase I study in patients with HER2‐positive cancer, PRS‐343 demonstrated single‐agent antitumor activity, including partial responses, and was well‐tolerated at doses up to 8 mg/kg q2w 20 …”
Section: Mechanism Of Action Of Bispecific Antibodies In Oncologymentioning
confidence: 99%
“…Currently, atezolizumab is the only FDA-approved immune checkpoint inhibitor for BC (TNBC) treatment. Out of many new drugs that are under clinical trial, margetuximab (MGA-H22) received FDA approval for fast track investigation on its potency to treat HER2 + metastatic BC [146][147][148]. This is a novel HER2-targeted monoclonal antibody tailored to enhance the binding affinity to multiple sites by mediating activation of Fc-γ receptors.…”
Section: Pd-1/pd-l1 and Her2 Crosstalk In Breast Cancermentioning
confidence: 99%
“…Developing mathematical models in terms of the biomarkers related to disease prognosis (e.g., PDL1 expression + high Tregs + less TILs = poor prognosis), and treatment response (e.g., presence of TILs favors response to trastuzumab) can help to identify patient cohorts that will benefit from a certain therapy [146].…”
mentioning
confidence: 99%
“…A FAP-targeted immunocytokine with trimeric single-chain 4-1BBL has recently started phase I clinical testing in cancer patients, but the product did not exhibit a conditional activation of the 4-1BBL moiety 84 . A fusion protein of trastuzumab with a 4-1BB-specific anticalin™ has been described 85 , which had shown antigen-dependent modulation of 4-1BB agonistic activity in vitro and which has recently started clinical trials 85 .…”
Section: Discussionmentioning
confidence: 99%
“…The approach described in this article should be generally applicable to members of the TNF superfamily. Alternative approaches may involve bispecific antibodies 93,94 , the modular use of small protein domains 85,95 or of chemically-modified bicyclic peptides 96 . Members of the TNF receptor superfamily are particularly suited for cooperative activation strategies in view of their homotrimeric structure and clustering-driven activation properties [97][98][99] .…”
Section: Discussionmentioning
confidence: 99%